"Don't touch that dial": Accommodating musical preferences in interpersonal relationships. (September 2016) - Denes, Amanda; Gasiorek, Jessica; Giles, Howard
How we adapt our behavior for others' preferences in interpersonal interactions—particularly when those preferences differ from our own—can be a means to nonverbally communicate our attention, interest, and concern for them. Invoking communication accommodation theory (CAT), this vignette study examined how relational closeness and attraction influenced accommodation to others' musical tastes. One hundred and fifty-nine individuals completed questionnaires assessing their imagined musical accommodation in response to the scenarios detailed in the vignettes. As hypothesized, we found that accommodation of musical preferences was generally predicted by how relationally close or attractive these others were considered to be. However, how important individuals self-reported music to be did not moderate these results. These findings suggest that accommodating to another person's musical tastes may be a nonverbal way of showing concern for another's preferences and may communicate closeness and attraction. In this way, musical accommodation may help build, sustain, and manage social relationships. These results extend CAT into a new applied domain and the implications of the findings are discussed.